2015
DOI: 10.4038/jnsfsr.v43i2.7942
|View full text |Cite
|
Sign up to set email alerts
|

ACE-inhibitory activity of milk fermented with Saccharomyces cerevisiae K7 and Lactococcus lactis subsp. lactis NBRC 12007

Abstract: Abstract:The angiotensin-I converting enzyme (ACE) inhibitory activity of the milk fermented with Lactococcus lactis subsp. lactis NBRC 12007 and Saccharomyces cerevisiae K7 in monoculture and co-culture was evaluated. Bovine full-fat milk was fermented with each strain in monoculture and co-culture at 30 ºC for 72 h, and the in vitro ACE inhibitory activity (%) of each milk sample was determined by a fluorogenic assay using H-(2)Abz-Acp(6)-Ala-Phe(4-NO 2 )-Leu-OH as the substrate. The ACE inhibitory percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The FAN content was found to be significantly and positively correlated (P < 0.01) with the ACE inhibitory activity. The high FAN level was indicative of a high proteolytic activity of the starter culture (Rasika et al, 2015), and this greatly increased the chance of ACE inhibitory peptide production (Fuglsang et al, 2002). The ACE inhibitory activity gradually decreased until the fermentation ended, possibly due to the depletion of raw materials for peptide production, inhibition of proteases or peptidases by the acidic environment, and the natural degradation of the ACE inhibitory materials.…”
Section: Discussionmentioning
confidence: 99%
“…The FAN content was found to be significantly and positively correlated (P < 0.01) with the ACE inhibitory activity. The high FAN level was indicative of a high proteolytic activity of the starter culture (Rasika et al, 2015), and this greatly increased the chance of ACE inhibitory peptide production (Fuglsang et al, 2002). The ACE inhibitory activity gradually decreased until the fermentation ended, possibly due to the depletion of raw materials for peptide production, inhibition of proteases or peptidases by the acidic environment, and the natural degradation of the ACE inhibitory materials.…”
Section: Discussionmentioning
confidence: 99%
“…Rasika et al [24] reported that the ACE inhibitory activity of the milk samples fermented with single or mixed cultures of Lb. lactis ssp.…”
Section: Lab Strainmentioning
confidence: 99%